2020
DOI: 10.1136/ijgc-2020-001623
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose adjuvant vaginal cylinder brachytherapy for early-stage non-endometrioid endometrial cancer: recurrence risk and survival outcomes

Abstract: ObjectiveThe aim of this study was to evaluate recurrence patterns and survival outcomes for patients with early-stage non-endometrioid endometrial adenocarcinoma treated with adjuvant high-dose rate vaginal brachytherapy with a low-dose scheme.MethodsA retrospective review was performed of patients with International Federation of Gynecology and Obstetrics (FIGO) stage I–II non-endometrioid endometrial cancer who received adjuvant vaginal brachytherapy with a low-dose regimen of 24 Gy in six fractions from No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As depicted in the nomogram, serous carcinoma has the lowest score of all the histological subtypes. Previous studies have confirmed that NEEC has no significant correlation with estrogen compared with EEC, and it is more commonly occurred in menopausal and postmenopausal women [ 12 , 13 ]. Therefore as shown in this study, older patients (66-) are more possible developed NEEC, and the prognosis were worse than that of younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…As depicted in the nomogram, serous carcinoma has the lowest score of all the histological subtypes. Previous studies have confirmed that NEEC has no significant correlation with estrogen compared with EEC, and it is more commonly occurred in menopausal and postmenopausal women [ 12 , 13 ]. Therefore as shown in this study, older patients (66-) are more possible developed NEEC, and the prognosis were worse than that of younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the advanced stage had a higher recurrence rate (43.7% vs. 12%, p < 0.001) and overall death rate (31.2% vs. 13%, p = 0.006); the mean times to recurrence (11.57 ± 9.12 vs. 30.24 ± 30.33, p = 0.001) and death (26.50 ± 21.07 vs. 64.00 ± 68.84, p = 0.024) were also significantly shorter. We reviewed the current literature regarding prognostic factors for ECCC survival and found that LVSI [ 22 , 26 28 , 30 , 31 ], disease stage [ 31 33 ], age [ 33 ], PWC [ 13 , 27 , 34 ], and MI [ 22 , 31 , 32 , 35 ] were correlated with ECCC prognosis. Notably, both ECCC and serious uterine carcinoma have been analyzed in most of these studies.…”
Section: Discussionmentioning
confidence: 99%